3D conformation and crystal interaction insights into drug development challenges for HCV drug analogues via molecular simulations - Richard S. Hong; Alessandra Mattei; Mark E. Tuckerman; Ahmad Y. Sheikh (Communications Chemistry)
Abstract ABT-333 and ABT-072 are two potent non-nucleoside NS5B polymerase inhibitors designed for the treatment of the hepatitis C virus (HCV). These structural analogs differ only by a minor substituent change, which disrupts the planarity of the naphthyl group on the ABT-333 compound through the addition of a more flexible trans-olefin substituent. However, this minor change leads to significant differences in their conformational preferences and intermolecular interactions, resulting in a ripple effect with drug development implications, ranging from crystal polymorphism and low aqueous solubility to formulation development challenges. In this article, we demonstrate how a suite of molecular simulation approaches, including crystal structure prediction augmented with a new hydrate CSP algorithm, free-energy perturbation, molecular dynamics (MD) based solubility predictions, and topological assessment to evaluate surface re-crystallization tendencies, provide key atomistic-level insights into the differentiated performance of the two analogs. Through this study, we establish the importance of end-to-end physics-based modeling, which involves explicit considerations of 3-D structure and crystal packing interactions. This approach provides structural and energetic insights into the physicochemical properties and drug development challenges faced when designing best-in-class drug molecules.